2018
DOI: 10.14218/jcth.2018.00010
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease: Epidemiology, Liver Transplantation Trends and Outcomes, and Risk of Recurrent Disease in the Graft

Abstract: In parallel with the rising prevalence of metabolic syndrome globally, nonalcoholic fatty liver (NAFL) disease is the most common chronic liver disease in Western countries and nonalcoholic steatohepatitis (NASH) has become increasingly associated with hepatocellular carcinoma. Recent studies have identified NASH as the most rapidly growing indication for liver transplantation (LT). As a hepatic manifestation of the metabolic syndrome, NAFL disease can be histologically divided into NAFL and NASH. NAFL is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…Global epidemiology studies have suggested that NAFLD can progress to liver cirrhosis (LC) or HCC, although the exact burden of NAFLD‐related LC and HCC remains uncertain. A study based on the US population revealed that NAFLD is one of the most common etiologies (59%) for HCC, and data from the Scientific Registry of Transplant Recipients for 2002 to 2017 demonstrate that the prevalence of HCC in NASH increased 11.5‐fold and that liver transplant that was due to HCC increased 8.5‐fold in the United States . NASH has also become the fastest growing cause of advanced liver complications .…”
Section: Resultsmentioning
confidence: 99%
“…Global epidemiology studies have suggested that NAFLD can progress to liver cirrhosis (LC) or HCC, although the exact burden of NAFLD‐related LC and HCC remains uncertain. A study based on the US population revealed that NAFLD is one of the most common etiologies (59%) for HCC, and data from the Scientific Registry of Transplant Recipients for 2002 to 2017 demonstrate that the prevalence of HCC in NASH increased 11.5‐fold and that liver transplant that was due to HCC increased 8.5‐fold in the United States . NASH has also become the fastest growing cause of advanced liver complications .…”
Section: Resultsmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ affection worldwide in the recent decades. On the other hand, liver disease associated with obesity and the consequent evolution to steatosis, steatohepatitis, cirrhosis and hepatocellular carcinoma has become one of the main causes of liver failure and transplantation in recent years, with the aggravating possibility of recurrence in the transplanted organ 36,37 . In our cross-sectional retrospective study, the NAFLD incidence evaluated by histological examination was 46.48% among the morbidly obese patients who underwent bariatric surgery, and 50% in the first timepoint of the paired longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of liver diseases has significantly changed over the last years owing to NAFLD continuously growing prevalence in parallel with the decline of chronic hepatitis C virus (HCV) thanks to the advent of highly-effective direct-acting antiviral agents [8]. NAFLD is a multi-system disease representing a relevant health care issue [39].…”
Section: Af and Vte In The Nafld Spectrummentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD), now the most common chronic liver disease (CLD) in developed countries, embraces a spectrum of histopathological conditions ranging from simple relatively benign simple steatosis to nonalcoholic steatohepatitis (NASH), which is associated with progression to fibrosis/cirrhosis and hepatocellular carcinoma [6]. NASH will be the leading cause for liver transplantation by 2020 [7,8]. NAFLD is independently associated with an increased risk of abnormalities of cardiac structure and function, including cardiac rhythm disorders (mainly AF) [9,10].…”
mentioning
confidence: 99%